Evaluation of Fenton Process in Removal of Direct Red 81 - Mohammad Ali Baghapour; Mansooreh Dehghani; zahra elhamiyan (Shiraz University of Medical Sciences, 2016)
Background: Dyes are visible materials and are considered as one of the hazardous components that make up the industrial waste. Dye compounds in natural water, even in very low concentrations, will lead to environmental problems. Azo dyes are compounds with one or more -N=N- groups and are used in textile industry. Because of its low price, solubility, and stability, azo dyes are widely used in the textile industry. Direct Red 81 (DR81) is one of the azo dyes, which is removed from bodies of water, using various methods. This study aimed to assess DR81 dye removal by Fenton oxidation and the effects of various parameters on this process. Methods: Decolorization tests by Fenton oxidation were performed at dye concentrations of 50, 500, 100 and 1000 mg/L; hydrogen peroxide concentrations of 0, 10, 30, 60 and 120 mg/L; iron (II) sulfate heptahydrate concentrations of 0, 3, 5, 20 and 50 mg/L; and pH levels of 3, 5, 7 and 10 for durations of 5, 10, 20, 30, 60 and 180 minutes. Results: The optimal condition occurred at a dye concentration of 20 mg/L, hydrogen peroxide concentration of 120 mg/L, bivalent iron concentration of 100 mg/L, pH of 3, and duration of 30 minutes. Under such conditions, the maximum dye removal rate was 88.98%. Conclusion: The results showed that DR81 could be decomposed and removed by Fenton oxidation. In addition, the removal of Direct Red 81 (DR81) depends on several factors such as dye concentration, reaction time, concentrations of hydrogen peroxide and iron, and pH